2005
DOI: 10.1074/jbc.m500796200
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Di- and Tri-methyl Lysine 36 of Histone H3 at Active Genes

Abstract: Methylation of lysine 4 of histone H3 (K4/H3) is linked to transcriptional activity, whereas methylation of K9/H3 is tightly associated with gene inactivity. These are well characterized sites of methylation within histones, but there are numerous other, less characterized, sites of modification. In Saccharomyces cerevisiae, methylation of K36/H3 has been linked to active genes, but little is known about this methylation in higher eukaryotes. Here we analyzed for the first time the levels and spatial distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
276
5
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 387 publications
(315 citation statements)
references
References 21 publications
26
276
5
3
Order By: Relevance
“…So far, these studies have revealed that actively transcribed chromatin regions are enriched in H3/K4 mono-, di-, or trimethylation, H3/K36 trimethylation, and monomethylation of H3/K9, H3/ K27, and H4/K20. The distribution of these marks over the transcribed region of genes is not equal; trimethylation of H3/K4 is enriched at the 5Ј end of transcribed regions and can serve as an indicator for transcription start sites, whereas H3/K36 methylation is enriched at the 3Ј end and may be linked to processing of the transcripts (Bannister et al 2005). In contrast to this, trimethylation of H3/K9, H3/K27, and H3/K79 is linked with repression (Barski et al 2007).…”
Section: Chromatin Modificationsmentioning
confidence: 81%
“…So far, these studies have revealed that actively transcribed chromatin regions are enriched in H3/K4 mono-, di-, or trimethylation, H3/K36 trimethylation, and monomethylation of H3/K9, H3/ K27, and H4/K20. The distribution of these marks over the transcribed region of genes is not equal; trimethylation of H3/K4 is enriched at the 5Ј end of transcribed regions and can serve as an indicator for transcription start sites, whereas H3/K36 methylation is enriched at the 3Ј end and may be linked to processing of the transcripts (Bannister et al 2005). In contrast to this, trimethylation of H3/K9, H3/K27, and H3/K79 is linked with repression (Barski et al 2007).…”
Section: Chromatin Modificationsmentioning
confidence: 81%
“…regions of active genes and peaked at the 3 0 end of genes, 40 and H3K79me3, a promoter mark, were all depleted in the aDMRs and aGENs (Fig. 3, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, active genes themselves possess a high enrichment of H3K4me3, which marks the transcriptional start site (TSS) [86,90]. In addition, H3K36me3 is highly enriched throughout the entire transcribed region [91]. The mechanisms by which H3K4me1 is laid down at enhancers is unknown, but work in yeast has provided mechanistic detail into how the H3K4 and H3K36 methyltransferases are recruited to genes, which in turn helps to explain the distinct distribution patterns of these two modifications ( Figure 3).…”
Section: Euchromatinmentioning
confidence: 99%